Resource deprivation in the home environment is associated with negative symptoms in outpatients with Schizophrenia - Lauren Luther; Zhixin Zhang; Sydney H. James; Luyu Zhang; Jennifer Standridge; Lauren Arnold; Ruth Condray; Daniel N. Allen; Gregory P. Strauss (Schizophrenia)
Abstract Limited negative symptoms treatment effectiveness may result from environmental resource deprivation that is a barrier for performing goal-directed, recreational, and social activities. This study showed that environmental resource deprivation in the home environment was greater for people with schizophrenia (n = 39) than 32 demographically-matched healthy controls (CN). Greater environmental resource reductions for performing goal-directed, recreational, and social activities were associated with greater negative symptoms, even after controlling for income and secondary negative symptom factors (depression, positive symptoms).